Felipe Santiago Gutiérrez visits Bogotá accepting Rafael Pombo’s invitation to found the Vázquez academy: a feminine theory of artistic production as a product of inter-atlantic dialogue - Fino Gómez, Carlos Orlando (Universidad de Boyacá, 2017)
This article analyses how the link between image and word was a basis for the production of aesthetic arguments between the Colombian writer Rafael Pombo and the Mexican painter Felipe Santiago Gutiérrez. This was the case when the later visited Bogotá between 1873 and 1875 in order to found the Vásquez Academy. Pombo’s feminine theory of artistic production is grounded on two historical facts: the foundation of the first Colombian female academy by Gutiérrez, and the painter’s artistic work, which drawn upon both the emerging European impressionism and a Latin American awareness coinciding with what recognizable in José Marti’s thought since 1875. These two sources are reflected in a couple of examples studied here (“Portrait of José María Espinoza” and “The Hunter of the Andes”). The present work aims to demonstrate that the aforementioned theory emerged from the dialogue image-text and text-artistic creation, feeding the aesthetic discussion on the relationship between humans and nature. In the particular case considered here, this association arose as a proposal related to the search for an order of the world in the foundational ideas of the American republics.